Sulphenylation of CypD at Cysteine 104: A Novel Mechanism by Which SO2 Inhibits Cardiomyocyte Apoptosis - Lv, Boyang; Peng, Hanlin; Qiu, Bingquan; Zhang, Lulu; Ge, Mei; Bu, Dingfang; Li, Kun; Yu, Xiaoqi; Du, Jiantong; Yang, Liu; Tang, Chaoshu; Huang, Yaqian; et al. (Frontiers in Cell and Developmental Biology, 2022)
Objectives: The study was designed to explore the role of endogenous gaseous signaling molecule sulfur dioxide (SO2) in the control of cardiomyocyte apoptosis and its molecular mechanisms. Methods: Neonatal mouse cardiac myocytes (NMCMs) and H9c2 cells were used in the cell experiments. The endogenous SO2 pathway including SO2 level and the expression of SO2-generating enzyme aspartate aminotransferase 1/2 (AAT1/2) were detected in NMCMs. The apoptosis of cardiomyocytes was examined by a TUNEL assay. The cleavage and the activity of apoptotic proteins caspase-9 and caspase-3 were measured. The content of ATP, the opening of mitochondrial permeability transition pore (mPTP), and the cytochrome c (cytc) leakage were detected by immunofluorescence. The sulphenylation of cyclophilin-D (CypD) was detected by biotin switch analysis. The four CypD mutant plasmids in which cysteine sites were mutated to serine were constructed to identify the SO2-affected site in vitro. Results: ISO down-regulated the endogenous SO2/AAT pathway of cardiomyocytes in association with a significant increase in cardiomyocyte apoptosis, demonstrated by the increases in apoptosis, cleaved-caspase3/caspase3 ratio, and caspase3 activity. Furthermore, ISO significantly reduced ATP production in H9c2 cells, but the supplement of SO2 significantly restored the content of ATP. ISO stimulated mPTP opening, resulting in an increase in the release of cytc, which further increased the ratio of cleaved caspase9/caspase9 and enhanced the protein activity of caspase9. While the supplementation of SO2 reversed the above effects. Mechanistically, SO2 did not affect CypD protein expression, but sulphenylated CypD and inhibited mPTP opening, resulting in an inhibition of cardiomyocyte apoptosis. The C104S mutation in CypD abolished SO2-induced sulphenylation of CypD, and thereby blocked the inhibitory effect of SO2 on the mPTP opening and cardiomyocyte apoptosis. Conclusion: Endogenous SO2 sulphenylated CypD at Cys104 to inhibit mPTP opening, and thus protected against cardiomyocyte apoptosis.